Hard and soft locational factors, innovativeness and firm performance: an empirical test of Porter's Diamond model at the micro-level - Alexander Eickelpasch; Anna Lejpras; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper investigates predictions of Porter's Diamond model regarding the impact of locational factors on innovativeness and performance at the firm level. We formulate a structural equation model based on the relationships between locational conditions, e.g., transportation infrastructure, proximity to universities and research institutes, qualified labour, on the one hand, and innovativeness measured by new product or process development, number of patents, and firm performance in terms of market growth or profit assessment, on the other hand. Based on a sample of about 2,100 East German firms, we apply the partial least squares path modelling approach to test the proposed relationships. We find that particularly cooperation intensity at the local level spurs the innovativeness of firms; whereas in contrast to Porter's predictions, our results indicate that strong local competition and a locally focused market appear to impede the innovativeness and performance of firms.
Keywords: R30; L25; O30; 330; Hard and Soft Locational Factors; Innovativeness; Firm Performance; East German Firms; Structural Equation Modelling; Partial Least Squares Approach; Innovation; Unternehmensentwicklung; Standortfaktor; Neue Bundesländer